Solubility of Trivalent Am, Eu, and Sm in the Synthetic KAERI Underground Research Tunnel Groundwater - Kim, Hee-Kyung; Cho, Hye-Ryun; Cha, Wansik (Journal of nuclear fuel cycle and waste technology (Online), 2024)
The initial radionuclide migration quantity depends on the total amount of solubilized species. Geochemical modeling based on a thermodynamic database (TDB) has been employed to assess the solubility of radionuclides. It is necessary to evaluate whether the TDB describes the domestic repository conditions appropriately. An effective way to validate the TDB-based modeling results is through direct comparisons with experimentally measured values under the conditions of interest. Here, the solubilities of trivalent Sm, Eu, and Am were measured in synthetic KURT-DB3 groundwater (Syn- DB3) and compared with modeling results based on ThermoChimie TDB. Ln2(CO3)3·xH2O(cr) (Ln = Sm, Eu) solids were introduced into the Syn-DB3 and dissolved Sm and Eu concentrations were monitored over 223 days. X-ray diffraction analysis confirmed that the crystallinity of the solid compounds was maintained throughout the experiments. The dissolved Sm and Eu concentrations at equilibrium were close to the predicted solubilities of Sm2(CO3)3(s) and Eu2(CO3)3(s) based on the ThermoChimie TDB. The Am solubility measured under oversaturated conditions was comparable to the measured Eu concentrations, although they were measured under different experimental settings. More experimental data are needed for Am-carbonate solid systems with careful characterization of the solid phases to better evaluate Am solubility in domestic groundwater conditions.